The Impact of Financial Regulation on Indian Arbitral Institutions and Corporate Compliance - Zayoun, Bilal; Behera, Bijayananda (Journal of Global Economy, Business and Finance, 2024)
Arbitration is a legal process that promotes the resolution of private disputes, commonly employed for business conflicts, particularly in the context of multinational transactions. The recognition of this practice in India in the late 19th century and was subsequently extended to various parts of British India in 1908. The Arbitration and Conciliation Act 1996 was enacted in 1996 with the purpose of dealing with both domestic and international arbitration. International commercial arbitration is a substitute approach for settling conflicts between private entities that arise from business transactions across different countries. It enables parties to bypass legal proceedings in national courts. In the legal matter of Marriott International Inc. versus Ansal Hotels Limited, the party appealing the decision aimed to contest an order issued by a single judge. The appellant contended that the single petition for relief on multiple causes of action was not viable, as each contract constituted an autonomous agreement aimed at delivering services.